2022
DOI: 10.1186/s41938-022-00603-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simultaneous treatment of gamma irradiation and Bacillus thuringiensis on cotton leaf worm Spodoptera littoralis (Boisd.) (Noctuidae: Lepidoptera)

Abstract: Background The two biological control methods, inherited sterility technique (IST) and Bacillus thuringiensis (Bt), are considered as the two promising methods for lepidopteran pest management. Simultaneous treatment with both techniques was assessed against the cotton leaf worm, Spodoptera littoralis (Boisd.) (Noctuidae: Lepidoptera) compared to individual treatment for developing the lepidopteran management program. Results Pupation and adult em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The averages number of spermatophore per mated female moths was decreased by increasing the dose level to parent, while, the mating ability through F 1 generations not clearly influenced. In general the female and male moths are polygamy, irradiation treatment has negative impact of the male mating ability of S. littoralis (Sayed et al, 2022), Spodoptera litura (Sengupta et al, 2022) and Epiphyas postvittana (Stringer et al, 2013). The present results indicated that high doses of radiation 200 to 250 Gy exhibited lower in sperm transfer (spermatophore) in the P 1 generations compared to un-irradiated ones, however, in F 1 generation the mating ability was improved by increasing the spermatophore numbers of irradiated moths.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The averages number of spermatophore per mated female moths was decreased by increasing the dose level to parent, while, the mating ability through F 1 generations not clearly influenced. In general the female and male moths are polygamy, irradiation treatment has negative impact of the male mating ability of S. littoralis (Sayed et al, 2022), Spodoptera litura (Sengupta et al, 2022) and Epiphyas postvittana (Stringer et al, 2013). The present results indicated that high doses of radiation 200 to 250 Gy exhibited lower in sperm transfer (spermatophore) in the P 1 generations compared to un-irradiated ones, however, in F 1 generation the mating ability was improved by increasing the spermatophore numbers of irradiated moths.…”
Section: Discussionmentioning
confidence: 47%
“…Over the last decades, the intensive uses of pesticides to control the cotton leaf worm and other Lepidopteran species have been created many adverse effects on the environment problems and developed resistance to this insect (Sayed et al, 2020). Many attempts have been done to substitute the chemical control methods with environment-friendly tactics against those harmful pests (Sayed et al, 2022). Ionizing radiation is considered as a modern promising technology for insect population suppression as an autocidal control methods using sterile insect technique (SIT), which provide safe, sustainable and successful alternative methods in insect pest management (Robinson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%